Molecular characterization and recombinant expression of Babesia ovis SBP4 protein as a potential serodiagnostic antigen - Ozubek, Sezayi; Keskin, Sercan; Ulucesme, Mehmet Can; Eyvaz, Arda; Alatas, Mehmet; Doymaz, Mehmet Ziya; Aktas, Munir (Nature Portfolio, 2025)
Ovine babesiosis caused by Babesia ovis is a tick-borne disease that affects sheep in enzootic regions of Southern Europe, Middle East, and Asia, resulting in significant economic loss. Despite its clinical relevance, only a few useful serological markers are available for accurate diagnosis. In the present study, we characterized the B. ovis spherical body protein 4 (SBP4) using in silico, molecular, and immunological approaches, and evaluated its preliminary activity with sera naturally infected sheep, suggesting its potential for future serodiagnostic application. The full-length sbp4 gene was identified via genome analysis, revealing a 984 bp intronless open reading frame encoding a 327-amino acid protein with a predicted signal peptide. Codon-optimized for expression in Escherichia coli, the sbp4 gene was cloned and inserted into the pET-29b(+) vector. Expression in Escherichia coli C43(DE3) produced soluble recombinant rBoSBP4 protein, which was purified via affinity chromatography. The similar to 37 kDa protein was confirmed by SDS-PAGE and recognized by anti-His antibodies. Western blot and indirect ELISA using sera from naturally B. ovis-infected sheep demonstrated that rBoSBP4 is specifically recognized during infection, whereas negative control sera showed no reactivity. The immunization of rabbits with rBoSBP4 also induced a strong antibody response, as determined by ELISA. These results indicate that rBoSBP4 is both immunogenic and antigenically specific, supporting its potential utility in the development of serological diagnostic assays for ovine babesiosis.
Keywords: Babesia ovis; ELISA; SBP4; Serodiagnosis; Ovine babesiosis